2018
DOI: 10.1021/acs.langmuir.8b01830
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Soft Glassy Dynamics of an Aqueous Laponite Dispersion

Abstract: Synthetic hectorite clay Laponite RD/XLG is composed of disk-shaped nanoparticles that acquire dissimilar charges when suspended in an aqueous medium. Owing to their property to spontaneously self-assemble, Laponite is used as a rheology modifier in a variety of commercial water-based products. In particular, an aqueous dispersion of Laponite undergoes a liquid-to-solid transition at about 1 vol % concentration. The evolution of the physical properties as the dispersion transforms to the solid state is reminis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
101
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(108 citation statements)
references
References 175 publications
3
101
0
Order By: Relevance
“…Lastly, we also obtain a cryo-TEM image of a high concentration LAPONITE ® dispersion so as to directly relate a microstructure to the rheological findings. (13). A particle of LAPONITE ® has a disc-like shape with a diameter in the range of 25-30 nm and a thickness of about 1 nm (13).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lastly, we also obtain a cryo-TEM image of a high concentration LAPONITE ® dispersion so as to directly relate a microstructure to the rheological findings. (13). A particle of LAPONITE ® has a disc-like shape with a diameter in the range of 25-30 nm and a thickness of about 1 nm (13).…”
Section: Introductionmentioning
confidence: 99%
“…However, Suman and Joshi (13) analyzed the SAXS results and, based on the findings of Greene et al (33), observed that decoupling of intensity into a product of form factor and structure factor is a poor approximation for a disk-like particle having aspect ratio around 25, which also possess dissimilar charges. The very fact that Greene et al (33) suggest that, owing to high aspect ratio and high concentration of the particles, decoupling approximation leads to spurious peaks in structure factor, Suman and Joshi (13) The introduction of salt in clay dispersion greatly influences the aggregation dynamics. This has resulted in numerous studies exploring salt-clay interactions (35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The investigated system is a synthetic clay that dispersed in water originates a charged colloidal system characterized by a strong anisotropy due to the shape of the nano-disc particles (with a 25:1 ratio) and due to the inhomogeneity of the charges (negative and positive respectively distributed on the faces and rims [10]) that determines a microscopic competition between directional attractive and repulsive interactions. Laponite ® peculiar phase diagram has been largely investigated both experimentally [10][11][12][13][14][15][16][17][18] and theoretically [19][20][21][22][23][24][25][26]. The system spontaneously evolves towards different arrested states depending on the clay concentration and ionic strength.…”
mentioning
confidence: 99%